ANALISIS GAMBARAN KONSEP DIRI PADA KLIEN YANG MENJALANI TERAPI HEMODIALISA - Andro Ruben Runtu (Universitas Pahlawan Tuanku Tambusai, 2022)
Hemodialysis aims to improve the patient's quality of life, not treat it. This therapy requires time, patience, cost and the length of the hemodialysis process. In the same routine, the same environment, the same people, high costs and no support from the family, these are the things that must be faced by patients undergoing hemodialysis therapy, which can cause boredom that can affect or disrupt the client's self-concept. This study aims to analyze the self-concept description of clients undergoing hemodialysis therapy. Descriptive research design with a total sample of 41 people, with the total sampling technique. Based on the results, it was shown that 27 respondents (66%) did not have self-concept or positive self-concept and 14 respondents (34%) had negative self-concept. Based on the results of the conclusions with the support and motivation from the family can minimize the occurrence of disturbances of self-concept in clients. Keywords: Chronic kidney failure, hemodialysis, self-concept